2011
DOI: 10.1021/ma202031w
|View full text |Cite
|
Sign up to set email alerts
|

Radii of Gyration of Ring-Shaped Polystyrenes with High Purity in Dilute Solutions.

Abstract: Ring polystyrenes (PSs) were synthesized by anionic polymerization technique and purified with preparative size-exclusion chromatography (SEC). Seven ring PSs with their weight-average molecular weight (M w ) ranging from 17k to 570k were prepared and they were confirmed to have high purities all over 96% by liquid chromatography at the chromatographic critical condition (LCCC) analyses. Their radii of gyration (R g s) were determined in benzene-d 6 as a good solvent and in cyclohexane-d 12 or cyclohexane-h 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
99
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(115 citation statements)
references
References 52 publications
15
99
0
1
Order By: Relevance
“…The statistical average, or mean value, of the radius of gyration has been theoretically deduced for various polymer architectures. [13][14][15] These theoretical results have been verified by experiments [16][17][18][19][20] and by simulations. 21,22 On the other hand, much less attention has been paid to deviation/fluctuation of the radius of gyration.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…The statistical average, or mean value, of the radius of gyration has been theoretically deduced for various polymer architectures. [13][14][15] These theoretical results have been verified by experiments [16][17][18][19][20] and by simulations. 21,22 On the other hand, much less attention has been paid to deviation/fluctuation of the radius of gyration.…”
Section: Introductionmentioning
confidence: 75%
“…When we approximate Eq. (19) with the Gaussian distribution (namely, a quadratic expression), the mean value and the standard deviation take the following form:…”
Section: Discussionmentioning
confidence: 99%
“…As such, no precipitation or appreciable collapsing is to be expected. The same temperature was used in ref 26. We note, however, that a systematic study of the isotope effect the θ -decrement upon cyclization as well as the presence of knots 7,52 and its molecular weight dependence, although interesting, has not been pursued at this stage as it was not within the scope of the present investigation.…”
Section: Resultsmentioning
confidence: 99%
“…[50][51][52][53][54] Rings can be either knotted or unknotted and they cannot interconvert between different topologies without bond breaking and reformation. As a result, theoretical studies of rings using the Gaussian chain model suffer from the inability to account for these topological constraints.…”
Section: Partitioning Of Ring Polymersmentioning
confidence: 99%
“…It was shown that, even in the absence of excluded volume interactions, the size of rings do not scale with chain length N n with n = 0.5 as predicted by the Gaussian chain model, instead the exponent n 4 0.5 for rings. 50,53,54 Interestingly, Li et al 55 recently showed that while the conformational properties of unknotted rings differ from Gaussian chain rings, the confinement free energy of unknotted rings by a non-adsorptive slit follows the same scaling law as that of Gaussian chain rings.…”
Section: Partitioning Of Ring Polymersmentioning
confidence: 99%